A case of Manila type Mycobacterium tuberculosis infection in Japan. Issue 7 (5th June 2015) - Usami, Osamu; Nakajima, Chie; Endo, Shiro; Inomata, Shinya; Kanamori, Hajime; Hirakata, Yoichi; Uchiyama, Bine; Kaku, Mitsuo; Suzuki, Yasuhiko; Hattori, Toshio
Key Clinical Message A 76‐year‐old Japanese woman contracted a Mycobacterium tuberculosis (TB, Manila type) infection in Japan, despite never having traveled. However, her son was treated for TB in the Philippines 3 years before he stayed at her house. Spoligotyping allows us to identify the TB genotype and identify the route of infection.